2020
DOI: 10.1017/s0008423920000220
|View full text |Cite
|
Sign up to set email alerts
|

Soft Balancing, Binding or Bandwagoning? Understanding Institutional Responses to Power Disparities in the Americas

Abstract: What strategies will states pursue in managing their relations with more powerful neighbours? International Relations scholarship identifies a wide range of policy options open to “secondary states,” including soft balancing, bandwagoning and institutional binding. We provide a conceptual framework to distinguish between these similar and often conflated institutional strategies on the basis of two dimensions: threat perception and inclusiveness. We then apply this framework to the inter-American system. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…It maintains linkages with and wields leverage over the other member states as well as the OAS Secretariat, which is not only located in Washington next to the White House, but also dependent on US financial contributions (Closa and Casini, 2016). However, the scholarship on inter-American relations has shown that, despite the great asymmetry between the United States and Latin American countries, the United States rarely gets what it wants without the support of key Latin American states that wield great influence on delimited sub-regions, such as Brazil in South America and Mexico in Central America (Levick and Schulz, 2020;Long, 2017;Palestini, 2020;Shaw, 2004).…”
Section: Regional Powersmentioning
confidence: 99%
“…It maintains linkages with and wields leverage over the other member states as well as the OAS Secretariat, which is not only located in Washington next to the White House, but also dependent on US financial contributions (Closa and Casini, 2016). However, the scholarship on inter-American relations has shown that, despite the great asymmetry between the United States and Latin American countries, the United States rarely gets what it wants without the support of key Latin American states that wield great influence on delimited sub-regions, such as Brazil in South America and Mexico in Central America (Levick and Schulz, 2020;Long, 2017;Palestini, 2020;Shaw, 2004).…”
Section: Regional Powersmentioning
confidence: 99%
“…However, when it comes to secondary states strategies new concepts have proliferated, most of them overlapped and often ambiguous terms (Levick and Schulz, 2020). For instance, besides those already mentioned, Mearsheimer (2001) deals with buck-passing -in which the endangered great power tries to get another state to shoulder the burden of deterring or defeating the threatening state; with appeasement or accommodation -in this policy the appeaser aims to modify the behavior of the aggressor by conceding it power, in the hope that this gesture will make the aggressor feel more secure, thus dampening or eliminating its motive for aggression.…”
Section: From Balancing To Accommodation Policymentioning
confidence: 99%
“…Vol 8 Issue 12 DOI No. : 10.24940/theijhss/2020/v8/i12/HS2012-024 December, 2020 Levick andSchultz (2020 quoting Ikenberry, 2001 3 ) add institutional binding policy -this one happens when states cooperate with the hegemon not because they feel threatened but to achieve mutual gains. Different from balancing in its variants, soft and hard balancing, institutional binding, and accommodation are inclusive policies.…”
Section: From Balancing To Accommodation Policymentioning
confidence: 99%
See 1 more Smart Citation